Erosion Prediction And Land Conservation Planning Using The Usle Method In The Cikamiri Sub-Watershed - Yogina Lestari Ayu Situmorang; Akhmad Fauzan Mirai; Sarah Fitri Soerya (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose: This study aims to predict erosion levels and formulate land conservation directions in the Cikamiri Sub-Watershed as an effort to control land degradation and reduce the risk of hydrological disasters. This study is important considering the high potential for erosion that can trigger sedimentation, landslides, and floods in the Cikamiri Watershed area. Methodology: The study used a spatial quantitative approach with the Universal Soil Loss Equation (USLE) method based on Geographic Information Systems (GIS). The analyzed parameters included rainfall erosivity (R), soil erodibility (K), slope length and steepness (LS), crop management (C), and soil conservation practices (P). Furthermore, erosion control strategies were formulated using SWOT analysis based on the internal and external conditions of the study area. Results: The prediction results showed that the Cikamiri Sub-Watershed was dominated by a very slight erosion hazard level of 43%, while very severe erosion reached 23%, distributed in areas with steep slopes and residential areas. Findings: Land cover factors, slope steepness, and the low presence of vegetation cover in certain areas were the dominant factors influencing erosion levels. Novelty: This study integrates USLE- and GIS-based erosion prediction with SWOT analysis to produce more applicable land conservation directions at the sub-watershed level. Originality: Describes the new or innovative elements of the research that distinguish it from previous studies. This can involve new approaches, new methods, or new findings. Conclusion: Erosion control in the Cikamiri Sub-Watershed needs to be directed through vegetation strengthening, the implementation of soil conservation, spatial planning management, and sustainable community involvement. Type of Paper: Research article.